Pemberdayaan Ekonomi Masyarakat melalui Pengembangan Produk dan Pemasaran Kue Baruasa di Desa Sampulungan: Community Economic Empowerment through Product Development and Marketing of Kue Baruasa in Sampulungan Village - Nurdin, Nani Harlinda; Hamson, Zulkarnain; Said, Miah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Most of the kue baruasa micro businesses are still traditionally produced and use simple equipment, and the management of the marketing system still relies on word of mouth, so production and market penetration are still low. To overcome these problems, the PKM team designed strategies and techniques for developing kue baruasa products through production support tools and innovative marketing management through training and mentoring so that both partners can understand today's marketing using technological advances. These two PKM program designs can contribute to developing production quality, quality, and quantity to meet market needs. The objectives of this PKM program are to assist partners in applying technology in production, help partners obtain production support tools, and help partners improve the quality of their production by adopting the Production and Marketing Optimisation System offered as a result of this PKM research and activities.